Innovative activity in education: project method (Journal of Educational Sciences, 2019)
The article considers the teaching issues of 2nd year students of Kazakh language sections who learns the Russian language as non-native. The use of new ways in educational innovation activity provides great opportunities for a deeper approach to teaching students to a non-native language. Project method admitted as one of innovative methods. The history of the application of the project method in education began in the nineteenth century. A great contribution to the development of the project method was made by American educators J. Dewey, his student W. Kilpatrick. In the twenty-first century, this method has been updated and is associated with innovation.On the basis of the project method of professional Russian studying in the Kazakh audience, it is possible to achieve positive results in learning, arouse students' interest to the subject of study, prepare students for future professional activities, raising patriotism and social responsibility.  The application procedure for students to choose from the tasks of preparing a scientific work or a business project in Russian is methodically described. The attention is focused on the methodological competence of the teacher in the management of students’ activities and on-step methodological and research counseling.  More than 100 students of the Higher School of Economics and Business took part in the experimental and pedagogical work.Key words: educational innovations, project method, educational project, business project.